2002
DOI: 10.1103/physrevlett.89.035501
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior in Thin Films of Cylinder-Forming Block Copolymers

Abstract: We have experimentally determined a phase diagram for cylinder-forming polystyrene-block-polybutadien-block-polystyrene triblock copolymer in thin films. The phase behavior can be modeled in great detail by dynamic density functional theory. Deviations from the bulk structure, such as wetting layer, perforated lamella, and lamella, are identified as surface reconstructions. Their stability regions are determined by an interplay between surface fields and confinement effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

46
653
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 503 publications
(700 citation statements)
references
References 35 publications
46
653
1
Order By: Relevance
“…36 Dimensionality is another crucial factor for categorizing the confinement systems for microphase-separated structures. Onedimensional (1D) confinement is a thin film in which the substrate surface can be chemically modified to induce wetting of one of the phase-separated domains inside the film, 37,38 which is known as chemical asymmetry. The film thickness can also act as the confinement.…”
Section: Morphologies Of Bcp Under Confinementmentioning
confidence: 99%
“…36 Dimensionality is another crucial factor for categorizing the confinement systems for microphase-separated structures. Onedimensional (1D) confinement is a thin film in which the substrate surface can be chemically modified to induce wetting of one of the phase-separated domains inside the film, 37,38 which is known as chemical asymmetry. The film thickness can also act as the confinement.…”
Section: Morphologies Of Bcp Under Confinementmentioning
confidence: 99%
“…[1][2][3] On the other hand, in thin film, as additional parameters such as the film thickness and interfacial tension can play a significant role, it becomes more complicated to understand its morphology. [4][5][6] In † To whom correspondence should be addressed. E-mail: dlee@dankook.ac.kr Polymer(Korea), Vol.…”
Section: Introductionmentioning
confidence: 99%
“…36, No. 4,2012 particular, such BCP nanostructures can provide many possible applications such as nanolithography, 6-8 ultra high-density data storage media, 9-11 nanostructured templates, 12,13 and photonic crystals 14 when they are prepared in thin films. In general, to take BCP morphology in thermodynamic equilibrium for the feasible applications mentioned above, the thin film is thermally annealed above the glass transition temperature (T g ) of both blocks, so that its ordering quality is improved and defect levels become reduced.…”
Section: Introductionmentioning
confidence: 99%
“…5,18,19 Some studies have also shown that the orientation of microphase-separated structures can be controlled by exposing block copolymer films to solvent vapor and drying at a controlled evaporation rate. 13,18,[20][21][22][23][24][25][26][27] We have reported the experimental visualization of a threedimensional (3D) helical morphology for a polystyrene-block-polybutadiene-block-poly(methyl methacrylate) triblock terpolymer (SBM) using transmission electron microtomography (TEMT). 28 The TEMT observations revealed that the double-helical structure was composed of polybutadiene (PB) helical microdomains around hexagonal-packed polystyrene (PS) cylinder cores in a poly(methyl methacrylate) (PMMA) matrix, even though the block copolymer was not chiral.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques have been used to orient the cylindrical structures perpendicular to the substrate in the copolymer film, including surface affinity, 3-6 the application of shear force, 7 electric fields, [8][9][10][11] and magnetic fields. [12][13][14][15][16] In addition, surface roughness is critical for a vertical orientation. 17 However, few of these techniques can maintain the perpendicular orientation in the copolymer thick film over several micrometers.…”
Section: Introductionmentioning
confidence: 99%